Robotic building architecture in the age of automation - Claypool, Mollie (Edition Detail., 2019)
The use of robots in architecture is already commonplace: robots automate processes that were previously done manually. Complex shapes are created with the help of 3D printing while autonomous swarms of robots construct complex buildings. How does the use of robots affect the resulting structures; how does it affect the thinking of architects who work with robots? Robotic Building answers these questions with several practical examples. A final chapter explores the idea of architect as robot, the fully-automated home and similar concepts in which the robot merges with its environment and becomes part of our experience.